Relevansi Nilai-Nilai Piagam Madinah dan Pendidikan Islam pada Era Multikultural di Indonesia - Satria Amir Makmun Gunawan; Akhmad Nurul Kawakip (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2024)
Multicultural problems that often arise in Indonesia are conflicts between religions and within religions themselves. Various kinds of religious conflicts have adorned social life in Indonesia as a pluralistic country. These problems arise due to internal factors of bigotry of the religious adherents themselves, while extemal factors arise from various aspects, such as political, economic and social. This research aims to find out 1) History and multicultural values in the events of the Medina charter, 2) The role of an independent cumiculum in implementing multicultural education; and 3) The relevance of multicultural education values in the events of the Medina charter and the independent cuniculum for Islamic education in the multicultural era. This research uses a qualitative research approach with the type of library research by collecting various sources of information, both from books, joumal articles, reports and other sources of information that can support a comprehensive understanding of the research topic. The results showed that 1) The event of the Medina charter is a form of the Prophet Muhammad's serious efforts in realizing the value of tolerance. Where the purpose of the Prophet Muhammad SAW migrated to Medina for the mission of peace and justice for the people of Medina; 2) Strengthening the Pancasila Student Profile (P5) is an effort to internalize an understanding of the concept of multiculturalism, especially those contained in one of the main dimensions of the P5 program, namely the